THE USE OF VIDEO STREAMING LEARNING MEDIA IN GEOGRAPHIC LEARNING OUTCOMES BY NOTING LEARNING MOTIVATION - Ramadhani, Resita; Rohsulina, Pranichayudha; Rifa’i, Muh. Husyain (Universitas Veteran Bangun Nusantara, 2019)
The purpose of this study is to find out how to use streaming-based audio visual video media on the learning outcomes of geography subjects on the subject of hydrosphere dynamics by paying attention to students' learning motivation. The type of research used is experiment. The study was conducted on April 16 2018 until May 16 2018. In this study data was collected through several techniques, namely by using documentation methods, test methods, and questionnaires. The results of this study concluded that there were no differences in geography learning outcomes that applied streaming-based video audio visual media and did not use audio visual media. There is no difference in learning motivation that applies audio visual video, and there is a relationship between the use of audio visual media and learning outcomes on student learning motivation.